Positioning the North: Making British Geographical Knowledge of Australia in the Mid- Nineteenth Century - Skurnik Johanna (Routledge, 2025)
This chapter examines the formation of geographical and cartographical knowledge about the Australian continent by British actors in the mid-nineteenth century. These bodies of knowledge were constructed through the knowledge-work of several individuals and institutions spread across the globe. The central role played in this process by imperial civil servants stationed in the colonies and in Britain has been insufficiently remarked. The chapter investigates how, as part of wider bureaucratic developments, the civil servants functioned as knowledge-brokers as they facilitated, controlled, and coordinated the movements of material containing geographical and cartographic information. The chapter examines the circulation of information deriving from Augustus C. Gregory's government-funded North Australian Expedition (1855–1856). A term of comparison is provided by the regimes of mobility of the material originating from John McDouall Stuart's privately funded expeditions undertaken between 1859 and 1863. The chapter analyzes how the mediation of information via letters, manuscript and printed maps, newspaper clipping, and reports affected the processes of knowledge-making in different locations. The examination of the mobility of the material deriving from these expeditions illustrates the social and material processes that enabled or impeded the circulation of knowledge between different spaces of knowledge-making inside and beyond the British Empire.
Beyond Science and Empire: Circulation of Knowledge in an Age of Global Empires (1750-1945)